Anticancer properties of Dillenia suffruticosa (Griffith Ex. Hook. F. & Thomsom) Martelli - Ika Rahayu; Susana Elya Sudrajat; Kris Herawan Timotius (Phytomedicine Plus)
Background: Cancer is one of the most dreaded diseases worldwide. Herbal medicine represents a promising potential source for various types of cancer treatments. The herbal plant Dillenia suffruticosa shows potential in combating cancer progression. Objectives: This review aims to evaluate the anticancer effects of D. suffruticosa, including its extracts and bioactive compounds, on cellular responses, subcellular (mitochondrial) functions, and molecular aspects, as well as the associated molecular pathways. Methods: Previous reports on anticancer properties of D. suffruticosa were searched and screened from online sources, including PubMed, ScienceDirect, and Google Scholar. Results: The majority of anticancer studies on D. suffruticosa focus on breast cancer cell lines, particularly MCF7. The most effective extracts are those derived from ethyl acetate or dichloromethane. These extracts exhibit cytotoxic effects on the MCF7 breast cancer cell line in a dose- and time-dependent manner. They can induce cell cycle arrest and apoptosis. Their anticancer activities are also linked to the upregulation and downregulation of various signaling pathways, including the upregulation of SOD1, SOD2, NFκB, p53, p38, MAPK, and catalase, as well as the downregulation of Akt1. The major bioactive compounds present in these extracts, such as betulinic acid, koetjapic acid, lupeol, vitexin, tiliroside, and kaempferol, contribute to their anticancer properties. The presence of these compounds is crucial in determining the anticancer potential of the extract. Conclusion: Semipolar extracts and bioactive compounds of D. suffruticosa demonstrate potential as an effective intervention against cancer cells, particularly in the case of breast cancer. These extracts inhibit cancer cell growth, induce apoptosis, and target pathways like p53/p21, JNK, PI3K/AKT, and NFκB, with effects linked to mitochondrial dysfunction. Further research is needed to explore its roles in autophagy, cell differentiation, and the tumor microenvironment.